Synthesis, Magnetic Properties, and X‐ray Spectroscopy of Divalent Cobalt(II) and Nickel(II) Cubanes [MII4(HL2)4(OAc)4]1. Issue 11 (2nd March 2015) - Scheurer, Andreas; Korzekwa, Jana; Nakajima, Takayuki; Hampel, Frank; Buling, Anna; Derks, Christine; Neumann, Manfred; Joly, Loïc; Petukhov, Konstantin; Gieb, Klaus; Müller, Paul; Kuepper, Karsten; et al.
Abstract: Under anaerobic conditions, the reactions of cobalt(II) and nickel(II) acetate tetrahydrate with 2, 6‐pyridinedimethanol (H2 L 2, 3 ) in anhydrous acetonitrile afforded two tetranuclear metal(II) complexes [M II 4 (HL 2 )4 (OAc)4 ] (4 ; M II = Co 2+, Ni 2+ ) with a [M4 (μ3 ‐O)4 ] 4+ cubane core. X‐ray structural analyses revealed that both M II cubanes4a· 2CH3 OH and4b· 2CH3 OH are isostructural and crystallize in the tetragonal space group I 41 / acd with eight molecules in the unit cell. In the solid state, the orientation of the cubane cores of4 and the formation of a 3D framework were controlled by π–π interactions as well as intra‐ and intermolecular O–H··· O hydrogen bonds. Variable‐temperature magnetic susceptibility measurements revealed that the cubanes4 show a ferrimagnetic coupling scheme that leads to a diamagnetic ground state for both complexes. Core‐level X‐ray photoelectron spectroscopy confirmed that the Co and Ni ions in4a and4b are in a divalent state. X‐ray magnetic circular dichroism was performed to extract the spin and orbital contributions to the Co and Ni magnetic moments. We compared the experimental results of the local electronic structures around the Co 2+ ions in4a and the Ni 2+ ions in4b with charge‐transfer multiplet simulations. Abstract : Starting from 2, 6‐pyridinedimethanol (H2 L 2, 3 ) and metal(II) acetate tetrahydrates, divalent Co II and Ni II cubanes [M II 4 (HL 2 )4 (OAc)4 ] (4 ) have been synthesized through self‐organization. In addition to standard methods (e.g., IR, MS, X‐ray analysis), complexes4 were also characterized by magnetometry and X‐ray spectroscopic techniques, including XPS, XAS, and XMCD.